2013
DOI: 10.2478/s11535-013-0183-4
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Nimrod proteins bind bacteria

Abstract: Engulfment of foreign particles by phagocytes is initiated by the engagement of phagocytic receptors. We have previously reported that NimC1 is involved in the phagocytosis of bacteria in Drosophila melanogaster. We have identified a family of genes, the Nimrod gene superfamily, encoding characteristic NIM domain containing structural homologues of NimC1. In this work we studied the bacterium-binding properties of the Nimrod proteins by using a novel immunofluorescencebased flow cytometric assay. This method p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…Instead, the membrane of E. coli needs to be disrupted by antimicrobial peptides such as cecropin prior to there being a direct interaction between Eater and this bacterium (Chung and Kocks, 2011). Perhaps because of this reason some studies have found that the binding affinities of Nimrod family genes vary depending on whether the assay was carried out in vivo (with a full complement of hemolymph proteins) or in vitro (Chung and Kocks, 2011;Zsamboki et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, the membrane of E. coli needs to be disrupted by antimicrobial peptides such as cecropin prior to there being a direct interaction between Eater and this bacterium (Chung and Kocks, 2011). Perhaps because of this reason some studies have found that the binding affinities of Nimrod family genes vary depending on whether the assay was carried out in vivo (with a full complement of hemolymph proteins) or in vitro (Chung and Kocks, 2011;Zsamboki et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Genes in the Nimrod B subclass encode several NIM repeats but do not encode a transmembrane domain. Not much is known about the biology of Nimrod B genes, but a recent study showed that NimB2 binds E. coli in vitro, and that NimB1 binds both E. coli and Staphylococcus epidermidis (Zsamboki et al, 2013). Finally, genes in the Nimrod C subclass encode multiple NIM repeats and a transmembrane domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some members of the Nimrod gene family encode cell surface receptors with multiple transmembrane domains whereas others encode secreted proteins, and different members of this same protein family also recognize different combinations of pathogens (Estevez-Lao and Hillyer, 2014; Kocks et al, 2005; Kurucz et al, 2007; Zsamboki et al, 2013). Furthermore, some PRRs directly elicit immune effector processes such as phagocytosis and melanization, others activate intracellular signaling pathways that activate the transcription of immune effector genes, and yet others activate both effector and signaling pathways (Choe et al, 2002; Levashina et al, 2001).…”
Section: Pathogen Recognitionmentioning
confidence: 99%
“…By contrast, Nimrod C subclass receptors possess multiple NIM repeats and a transmembrane domain [19]. Two Nimrod C, Eater and NimC1 (Nimrod C1), have been characterized, and both of them are expressed in hemocytes and contributed to recognition and phagocytosis of bacteria [5,9,10].…”
Section: Introductionmentioning
confidence: 99%